THE IMPACT OF STUDENT EDUCATIONAL PSYCHOLOGY ON STUDENTS’ PERFORMANCE - Siti Nur Zahirah Omar; Afiqah Filzah Azhar; Afiqah Filzah Azhar; Noor Fadhilah Zainuddin; Ainin Sofia Zawawi (Journal of Islamic, Social, Economics and Development, 2024)
This study explores the intricate relationship between study habits, motivation, personality traits, and approach to learning that can influence the academic performance of students in UiTM Kelantan. There were 7,729 students’ population in the study overall, and 364 students from UiTM Kelantan made up the sample. For most university students, academic performance has emerged as a key worry for researchers. The results of this study show that academic performance and motivation have a substantial positive association (r = 0.817), with motivation having the most impact on academic achievement. Furthermore, regression analysis shows that r² = 0.668 and adjusted r² = 0.667, indicate that 66.7% of motivation has influenced students' academic performance at UiTM Kelantan, while another 33.3% is influenced by other factors. However, a moderately positive link has been found between academic performance and other criteria, which are study habits, personality traits, and approach to learning.